1998
DOI: 10.1046/j.1365-2648.1998.00540.x
|View full text |Cite
|
Sign up to set email alerts
|

Ethnic differences in breast self‐examination practice and health beliefs

Abstract: Thirty-two African American nurses (AAN) and 78 Caucasian nurses (CN) were compared on breast self-examination (BSE) practice and health beliefs. Relationships between these variables were also examined. The Health Belief Model provided the framework for the study. The sample is a subset of 269 women from a larger study. AANs were recruited from a professional nurses' group. CNs were recruited from a list of female employees of a university medical centre. The results of t-tests revealed no significant group d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
47
1
1

Year Published

2005
2005
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(54 citation statements)
references
References 41 publications
5
47
1
1
Order By: Relevance
“…We found no difference in BSE performance rate between the health personnel and GAS workers, and it can be said that almost all of those working in the health services had a common awareness level on this topic. Different results have been reported from studies investigating BSE frequency, the factors affecting it and the technique, in the general population and health personnel worldwide (Foxall et al, 1998;Fung, 1998;Odusanya and Tayo, 2001;Chong et al, 2002;Abu Salem and Hassan, 2007;Uncu and Bilgin, 2011); in our opinion these differences can be explained by the differences in cultural, and socio-economic factors.…”
Section: Discussionmentioning
confidence: 54%
See 2 more Smart Citations
“…We found no difference in BSE performance rate between the health personnel and GAS workers, and it can be said that almost all of those working in the health services had a common awareness level on this topic. Different results have been reported from studies investigating BSE frequency, the factors affecting it and the technique, in the general population and health personnel worldwide (Foxall et al, 1998;Fung, 1998;Odusanya and Tayo, 2001;Chong et al, 2002;Abu Salem and Hassan, 2007;Uncu and Bilgin, 2011); in our opinion these differences can be explained by the differences in cultural, and socio-economic factors.…”
Section: Discussionmentioning
confidence: 54%
“…There was no significant difference in performing BSE according to professional groups. The BSE rates in studies performed in our country on health personnel were between 56.1-92% (Kilic et al, 2006;Aslan et al, 2007;Uncu and Bilgin, 2011); in studies abroad this rate was reported to be between 89-93% (Foxall et al, 1998;Odusanya and Tayo, 2001;Chong et al, 2002;Abu Salem and Hassan, 2007). The results from the population in general changed between 17-61.7% (Fung, 1998;Dundar et al, 2006;Secginli and Nahcivan, 2006;Sirin et al, 2006;Discigil, 2007).…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…The frequency of BSE performance varies across ethnic and racial groups [9][10][11][12] although there are exceptions [13] and the data are complex. Several studies have shown that minority women report more frequent BSE than their majority counterparts [10,14,15].…”
Section: Breast Self-examination Among Subpopulations Of Womenmentioning
confidence: 99%
“…Several studies have shown that minority women report more frequent BSE than their majority counterparts [10,14,15]. Of women who were aware of breast cancer screening practices, for example, African Americans have reported more frequent BSE than Caucasians [16].…”
Section: Breast Self-examination Among Subpopulations Of Womenmentioning
confidence: 99%